Financiranje jedinica lokalne i područne (regionalne) samouprave - Šinković, Zoran (2019)
The territorial organization of modern states rests on the principles of decentralization, which includes the political, administrative and financial independence of the lower levels of government. It is a fundamental principle that no function, no job or task can be assigned to a certain level of government or body of government without the funds being provided. Local and regional selfgovernment are one of the most important areas of strategic importance for the development of democratic and quality public policies in the Republic of Croatia. The relationship between local and regional self-government and users can also be seen as a parallel process of strengthening the responsibility of local units for overall quality and «offering» public services in the local area. Therefore local and regional self-government have the right to various sources of funding in order to be able to carry out their tasks, or to provide, to a greater or lesser degree, better public services to their users.
Teritorijalna organizacija suvremenih država počiva na načelima decentralizacije, što obuhvaća političku, upravnu i financijsku neovisnost nižih razina vlasti. Temeljno je načelo da ni jedna funkcija, ni jedan posao ni zadatak ne može se dodijeliti određenoj razini vlasti ili tijelu državne vlasti a da se za to ne osiguraju novčana sredstva. Jedinice lokalne i područne (regionalne) samouprave predstavljaju jedno od strateški važnih područja ključnih za razvoj demokratskih i kvalitetnih javnih politika Republike Hrvatske. Odnos između jedinica lokalne i područne (regionalne) samouprave i korisnika može se promatrati i kao usporedni proces jačanja odgovornosti lokalnih jedinica za ukupnu kakvoću i „ponudu“ javnih usluga na lokalnom području. Stoga jedinice lokalne i područne (regionalne) samouprave imaju pravo na različite izvore financiranja kako bi mogle obavljati poslove iz svoje nadležnosti odnosno pružiti u većoj ili manjoj mjeri kvalitetnije javne usluge svojim korisnicima.
Bibliografske bilješke uz tekst ; bibliografija i izvori: str. 246-250.
Summary ; Sažetak.
Keywords: Lokalna uprava -- Regionalna uprava -- Decentralizacija -- Financiranje -- Fiskalna decentralizacija